(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize updated evidence regarding the epidemiology, pathogenesis, clinical characteristics, diagnosis, management, and indications for immune checkpoint inhibitor rechallenge in patients with immune checkpoint inhibitor related interstitial pneumonia. Methods: A narrative review was performed based on a systematic search of studies published between 2018 and 2026. Three clinical cases treated in Vietnam National Cancer Hospital are presented to illustrate common scenarios encountered in routine practice. Results: Immune checkpoint inhibitor-related interstitial pneumonia presents with highly heterogeneous clinical and radiological manifestations. Corticosteroids remain the mainstay of treatment. The decision to resume immune checkpoint inhibitor should be carefully individualized. Conclusions: Although rare, immune checkpoint inhibitor-related interstitial pneumonia is a treatment-altering complication that requires appropriate diagnostic work-up and therapeutic strategies.